Pathogenesis and biomechanics of adolescent idiopathic scoliosis (AIS) - Hefti, Fritz (Springer Berlin Heidelberg, 2013)
Adolescent idiopathic scoliosis is defined as a scoliosis that starts after the age of ten and has no clear underlying disease as a reason for its development. There is, however, a disparity between the growth of the vertebral bodies anteriorly and that of the posterior elements. The vertebral bodies grow faster than the posterior elements, resulting primarily in a lordosis. The diminished dorsal growth impedes the ventrally located vertebral bodies from increasing in height, forcing them to become distorted, i.e., rotate, in order to create space for themselves. This produces a rotational lordosis. The idea of looking at it in this way dates back to Somerville in 1952. Many recent studies have confirmed this idea and have shown that the spinal canal is shorter than the anterior ligament of the vertebral bodies. In a mathematical model of the spine it was demonstrated that—although the vertebral column in humans is still predominantly loaded in an axial direction—certain segments of the human spine (especially the backward inclined segments) are subject to dorsally directed shear loads as well. In addition to the antero-posterior difference in growth, there is also a deformation of the vertebral bodies itself in 3-D. This is probably secondary and not primary effects, but this question is still under discussion. For the treatment of scoliosis, the biomechanical principles of axial and transverse forces are used. The combination of axial and transverse loads is most beneficial for all curves. The axial forces provide most of the corrective bending moment when deformity is severe, while the transverse loads take over the correcting function when deformity is mild. The deformity angle of 53° is the break-even point for the axial and transverse loads. In more severe curves transverse forces become less and less efficient, while axial forces rapidly gain more and more effect.